2013
DOI: 10.2741/s407
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy for injured growth plate

Abstract: The growth plate has a limited self-healing capacity. Fractures sustained to the growth plate of young children could cause growth disturbances like angular deformity or growth arrest. Established therapies for injured physis only address related complications. Mesenchymal stem cells (MSCs) are multipotent cells which are capable of differentiating into various cells of the musculoskeletal system. Various MSC types have been tested for physeal regeneration, through in vivo lapine, porcine and ovine models, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…), role of TGFb and FGF in pre-differentiation and proliferation of MSC's, the best material and pore size of scaffolds, and the prochondrogenic effects of dynamic compression and hypoxia on MSC's proliferation. 63…”
Section: Future Directions Of Treatmentmentioning
confidence: 99%
“…), role of TGFb and FGF in pre-differentiation and proliferation of MSC's, the best material and pore size of scaffolds, and the prochondrogenic effects of dynamic compression and hypoxia on MSC's proliferation. 63…”
Section: Future Directions Of Treatmentmentioning
confidence: 99%
“…Recently, advancements in tissue engineering have enabled significant progress in the repair of injured growth plates. This is achieved by incorporating a combination of bone marrow mesenchymal stem cells (BMSCs) or chondrocytes and growth factors into biologically active scaffolds, aimed at constructing the growth-plate-regenerative cartilage that can replace the injured tissue and perform its original biological function ( Xian and Foster, 2006 ; Shukrimi et al, 2013 ; Wang et al, 2021 ). For instance, Erickson et al demonstrated the use of chitosan-genipin microgels loaded with stromal-cell derived factor-1α (SDF-1α) or transforming growth factor β3 (TGF-β3) ( Erickson et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%